The Influence of Situational Regulation on the Information Processing of Promotional and Preventive Self-Regulatory Individuals: Evidence From Eye Movements - Xiong, Jianping; Jin, Xiaokang; Li, Weili (Frontiers in Psychology, 2020)
Regulatory focus theory uses two different motivation focus systems — promotional and preventive — to describe how individuals approach positive goals and avoid negative goals. Moreover, the regulatory focus can manifest as chronic personality characteristics and can be situationally induced by tasks or the environment. The current study employed eye tracking methodology to investigate how individuals who differ in their chronic regulatory focus (promotional vs. preventive) process information (Experiment 1) and whether an induced experimental situation could modulate features of their information processing (Experiment 2). Both experiments used an eight-grid information processing task; half the grids were characterized by attribute-based information, and the other half by alternative-based information. We asked the subjects to view the eight grids based on their personal preferences and choose one of the virtual products presented in the grids to “purchase” by the end of each trial. Results of Experiment 1 show that promotional individuals do not exhibit a clear preference between the two types of information, whereas preventive individuals tend to fixate longer on the alternative-based information. In Experiment 2, we induced the situational regulatory focus via experimental tasks before the information processing task. The results demonstrate that the behavioral motivation is significantly enhanced, thereby increasing the depth of the preferred mode of information processing, when the chronic regulatory focus matches the situational focus. In contrast, individuals process information more thoroughly, using both processing modes, in the non-fit condition, i.e., when the focuses do not match.